Josephus Between Jerusalem and Rome: Cultural Brokerage and the Rhetoric of Emotion in the Bellum Judaicum (1.9–12) - Glas, J. E. (Histos, 2020)
This contribution aims to address the simple but far-reaching issue of the relationship between the Judaean and Graeco-Roman currents in Josephus’ Bellum Judaicum. It offers a new perspective on Josephus’ use of personal emotions in this work, in particular by looking at his outburst in BJ 1.9–12. It proposes to examine Josephus’ motivations for fashioning this passage in the way he did by (1) placing his compositional choices in their literary context, i.e., the broader historiographical outlook of the BJ, and (2) comparing his practice to the Graeco-Roman literature supposedly familiar to his intended audience in Rome. What I aim to show in this article is that Josephus uses emotions in a rhetorically calculated way with the intention of investing Roman readers in his account of the Judaean revolt against Rome.